The Impact of Discovery Learning on Students’ Motivation and Learning Outcomes in Vocational Education - Mas'ari Mas'ari; Adolf Bastian; Elvira Asril; Rizki Novendra; Yogo Turnandes; Nuris Fadhli Silangit (AL-ISHLAH: Jurnal Pendidikan, 2026)
Instructional models in vocational schools (SMKs) play a critical role in aligning students’ competencies with workplace demands. However, at SMK Negeri 2 Kepenuhan, student motivation and learning outcomes in the Vocational Fundamentals subject remained relatively low due to teacher-centered, traditional approaches. This study evaluates the effectiveness of the Discovery Learning model in improving motivation and learning outcomes among Grade X students in the Computer Network and Telecommunication Engineering program. A quantitative quasi-experimental design with a nonequivalent control group was employed. Two experimental classes were involved: one received group-based tasks, while the other completed individual tasks, both using the Discovery Learning model. Data were collected באמצעות motivation questionnaires, pretests, posttests, and observation sheets, and analyzed using N-gain and t-tests. The findings indicate significant improvements in both motivation and learning outcomes. The grouped class showed an increase in mean scores from 67 to 95 (N-gain = 0.90), while the individual class improved from 68 to 91 (N-gain = 0.70). Statistical analysis revealed significant differences (p 0.05). Observational data also demonstrated increased student engagement and active participation during learning activities. The results suggest that the Discovery Learning model effectively enhances student motivation and academic performance in vocational education. Its implementation fosters active learning and improves instructional quality, making it a viable innovative approach for vocational teaching contexts.